How is the injury severity scored? a brief review of scoring systems - Mohsen Ebrahimi; Hossein Pirazghandi; Hamid Reza Reihani (Reviews in Clinical Medicine, 2015)
The management of injured patients is a critical issue in pre-hospital and emergency departments. Trauma victims are usually young and the injuries may lead to mortality or severe morbidities. The severity of injury can be estimated by observing the anatomic and physiologic evidences. Scoring systems are used to present a scale of describing the severity of the injuries in the victims.We reviewed the evidences of famous scoring systems, the history of their development, applications and their evolutions. We searched electronic database PubMed and Google scholar with keywords: (trauma OR injury) AND (severity OR intensity) AND (score OR scale).In this paper, we are going to present a definition of scoring systems and discuss the Abbreviated Injury Scale (AIS) and Injury Severity Score (ISS), the most acceptable systems, their applications and their advantages and limitations.Several injury-scoring methods have been introduced. Each method has specific features, advantages and disadvantages. The AIS is an anatomical-based scoring system, which provides a standard numerical scale of ranking and comparing injuries. The ISS was established as a platform for trauma data registry. ISS is also an anatomically-based ordinal scale, with a range of 1-75. Several databases and studies are formed based on ISS and are available for trauma management research.Although the ISS is not perfect, it is established as the basic platform of health services and public health researches. The ISS registering system can provide many opportunities for the development of efficient data recording and statistical analyzing models.